The Teacher’s Pedagogic Competence in Teaching English at Secondary School Level - Nelza Gita Purnama; Risnawati Risnawati; Detti Lismayanti (Yayasan Karinosseff Muda Indonesia, 2021)
Pedagogical Competence is one kind of competencies that completely need to be mastered by teachers. Pedagogical competence refers to educational and teaching qualifications. One of the qualifications, the teachers should have the ability to manage and run the process of teaching and learning in the classroom. The aims of study are to know how the teacher’s pedagogical competence in teaching English. This study used Descriptive approach using mix method and the data were structured observation, questionnaire, and interview. The subjects of this study are an English teacher and 36 students of SMPN 16 Bengkulu Selatan. The findings of this study showed that the pedagogical competence of student is enough in medium category in can be seen at data interview and observation, and supported with the score of students’ perception on teachers’ pedagogical competence in teaching English were 27.2. The forms include: comprehend the qualities of understudies, this is finished utilizing an individual methodology, learning procedures, learning techniques, and learning materials that suit with students need. For aspects of teacher understanding of learning theory and learning principles which emphasizes very much on manuals, for the parts of educational program advancement educators just comprehend a little about the standards of educational plan improvement. Instructors aggregate schedule and exercise plans dependent on MGP. Based on the results of this study, the researcher suggested to the teachers that they should try to improve their strategy and competence when teaching in the class. The main problem of English Teachers are focusing only on the book instruction, not using English while teaching, and just giving the learners assignments without giving explanation in advance. There are also the solutions of all the problems like joining learning seminar or teacher forum.